Pengembangan E-Modul Berbasis Flipbook Pada Mata Pelajaran Produk Kreatif Dan Kewirausahaan - Bella Salsabila; Sri Wahyudi; Detri Amelia Chandra (Journal on Education, 2024)
Research on flipbook-based electronic modules (e-modules) in the learning of creative entrepreneurial products in class Implementation, 5) Evaluation. Research on the development of flipbook-based e-modules was carried out at the Ujungbatu vocational high school, Rokan Hulu Regency, Riau Province. The data collected was validation data tested by media experts and material experts. The results from both experts show the category is very feasible. The validation test carried out by media experts got a percentage of 85%, while the validation test score obtained by material experts got a percentage of 83%. Research on the development of digital flipbook-based e-modules involved 15 students in field tests by students getting a result of 84%, it can be concluded that the development of a flipbook-based e-module on the subject of creative entrepreneurial products is in the very suitable category for use